Cost-Effectiveness Analysis of Hepatic Arterial Infusion Chemotherapy of Infusional Fluorouracil, Leucovorin, and Oxaliplatin Versus Transarterial Chemoembolization in Patients With Large Unresectable Hepatocellular Carcinoma - Zhang, Haixia; Zeng, Xiaohui; Peng, Ye; Tan, Chongqing; Wan, Xiaomin (Frontiers in Pharmacology, 2022)
Purpose: The purpose of this study was to evaluate a cost-effectiveness analysis of hepatic arterial infusion chemotherapy with infusional fluorouracil, leucovorin, and oxaliplatin (FOLFOX-HAIC) as the first-line treatment for patients with large unresectable hepatocellular carcinoma (HCC) compared with transarterial chemoembolization (TACE). Methods: A Markov model was constructed to simulate the first-line treatment, disease recurrence, and survival of patients with large unresectable HCC. Transition probabilities were based on clinical trial data. The costs and health utilities were derived from the public literature. The outputs were total cost, quality-adjusted life-year (QALY), and incremental cost-effectiveness ratios (ICER). One-way and probabilistic sensitivity analyses were performed to examine model uncertainty. We also performed subgroup analyses. Results: The results of the base case analysis found that FOLFOX-HAIC increased overall costs by $9,381 and improved effectiveness by 1.01 QALYs compared with TACE. The one-way sensitivity analysis showed that the hazard ratio of progression-free survival and overall survival for FOLFOX-HAIC relative to TACE had the greatest impact on the ICER. Probabilistic sensitivity analysis found that the probability of FOLFOX-HAIC treatment being cost-effective was 99.54% at the willingness-to-pay threshold of $30,552/QALY. Patients in most subgroups favored FOLFOX-HAIC treatment because they had a more than 50% probability of being cost-effective compared to TACE, except for patients with negative hepatitis B infection. Conclusion: In conclusion, our study found that the FOLFOX-HAIC was a cost-effective option compared to TACE for patients with large unresectable HCC in China.